Awareness on bullying issue among the villagers in Kg Inanam Laut / Afiqah Safwanah Amir Kusin and Nur Afiqah Hafanan - Amir Kusin, Afiqah Safwanah; Hafanan, Nur Afiqah (2014)
The purpose of this thesis is to identify the awareness level of the villagers in Kg. Inanam Laut towards the school bullying issues. It is a comparison and association study that is to test whether or not one variable causes another to change. In this research, it aims to analyse whether peers and family behaviour, environment and social phenomenon, and trend and media will influence bullying issue among villagers in Kampung Inanam Laut, Sabah. A word count of the past researches was utilized in addition to the study on the factors influencing school bullying. Cross-sectional survey was used as a method to gather the data. Many conclusions were drawn based on the results of the research.